DESAIN PEMBELAJARAN PAI BERBASIS ONLINE DI MASA PANDEMI COVID 19 - Arifin, Syamsul (Rabbani: Jurnal Pendidikan Agama Islam, 2023)
Online learning in schools and colleges still requires improvement both technically, teaching methods, media and those related to the Islamic teaching and learning process in schools, when the world is faced with a pandemic that hits. The Covid-19 outbreak has had an impact on Islamic Education learning in schools. This situation forces the world of education to carry out an online learning process (online). The purpose of writing this article is to understand Online Learning at this time.